PENGARUH NILAI TUKAR DAN BI RATE TERHADAP TINGKAT INFLASI DI INDONESIA - Novegya Ratih Primandari; Ali Akbar; Novitha Aprillyani (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
The aim of this research is to determine the influence of the ExchangeRate and BI Rate on the Inflation Rate in Indonesia 2003-2022. The method usedis a quantitative method with multiple linear regression analysis tools. Based onthe research results, it is explained that the exchange rate has an insignificantpositive effect on the inflation rate in Indonesia, while the BI Rate has asignificant positive effect on the inflation rate in Indonesia. The coefficient ofdetermination is 0.734, it can be concluded that the contribution of the influenceof the exchange rate and the BI rate together to variations in changes in theinflation rate is 73.4%, the remaining 26.6% is caused by other factors notincluded in this research.